Analisis Tingkat Kesadaran Hukum Mahasiswa Ilmu Hukum UPI dalam Mematuhi Kewajiban Menggunakan Helm - Jayisy Miftah Faridz; M Rizkar Sutisna; Muhammad Razzaqqa Dhaffin; Muhammad Rifath Bajry (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the level of legal awareness among students of the Law Study Program at Universitas Pendidikan Indonesia (UPI) regarding their compliance with the obligation to wear helmets, based on Soerjono Soekanto’s indicators of legal awareness. A descriptive quantitative approach was applied using a Likert-scale questionnaire distributed to 71 respondents from the 2024 and 2025 cohorts. The findings show that students’ levels of legal knowledge and understanding fall into the medium category (78.87%), their legal attitudes into the high category (47.89%), and their legal behavior into the medium category (64.79%). These results indicate a gap between normative legal awareness and actual behavioral compliance. Overall, students’ legal awareness is at a moderate level, suggesting that legal understanding has not yet been fully internalized into consistent practice. The study recommends strengthening value-based and moral legal education so that students not only understand the law cognitively but also apply it as a guide for everyday behavior..